2007
DOI: 10.1007/s10765-007-0164-4
|View full text |Cite
|
Sign up to set email alerts
|

Isochoric Heat-Capacity Measurements for Pure Methanol in the Near-Critical and Supercritical Regions

Abstract: Isochoric heat-capacity measurements for pure methanol are presented as a function of temperature at fixed densities between 136 and 750 kg·m −3 . The measurements cover a range of temperatures from 300 to 556 K. The coverage includes the one-and two-phase regions, the coexistence curve, the near-critical, and the supercritical regions. A high-temperature, high-pressure, adiabatic, and nearly constant-volume calorimeter was used for the measurements. Uncertainties of the heat-capacity measurements are estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…This behavior was expected, since it is similar to observations for other heavy organic molecules at compressed-liquid state conditions. Our earlier studies [27,28] made us aware that linear behavior should be observed for internally consistent two-phase C V as a function of specific volume V . Thus, we took advantage of the linearity with respect to temperature to interpolate isochoric two-phase C V to integral values of temperature.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This behavior was expected, since it is similar to observations for other heavy organic molecules at compressed-liquid state conditions. Our earlier studies [27,28] made us aware that linear behavior should be observed for internally consistent two-phase C V as a function of specific volume V . Thus, we took advantage of the linearity with respect to temperature to interpolate isochoric two-phase C V to integral values of temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Since the method (experimental details, the physical basis and theory of the method, procedures, uncertainty assessment) and apparatus have been described in our earlier publications (see, for example [27,28]), only essential information will be briefly given here. Isochoric heat-capacity C V ( V,T ) measurements were performed with a high-temperature, high-pressure, and nearly constant-volume adiabatic calorimeter.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations